2021
DOI: 10.14710/jkm.v9i3.29341
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Berhubungan Dengan Perilaku Seksual Remaja Awal Di Lingkungan Prostitusi Bandungan Kabupaten Semarang

Abstract: Adolescents who lived in prostitution complex have unhealthy condition of environment that can affect their development, morality, and form improperly behavior. This study aimed to determine factors correlated with early adolescent sexual behavior in prostitution complex of Bandungan. This was an analytic-descriptive study with cross sectional study design. This study included 60 samples of early adolescents in Bandungan (10-14 years old) who were selected using proportional random sampling technique. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This shows that teenagers who smoke in Padukuhan Karangsari are in the mild category. Faridah (2017) states that many factors cause adolescents to smoke. Intrinsic factors that motivate adolescents to become smokers include gender factors, personality factors, work factors, and belief factors.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that teenagers who smoke in Padukuhan Karangsari are in the mild category. Faridah (2017) states that many factors cause adolescents to smoke. Intrinsic factors that motivate adolescents to become smokers include gender factors, personality factors, work factors, and belief factors.…”
Section: Resultsmentioning
confidence: 99%
“…On the analysis results of risky sex behavior variables, instruments of action parameters that lead to risky and non-risky adolescent sexual behavior were obtained through open and closed interviews with respondents. This interview was conducted to examine the confession of teenagers who have had premarital sexual intercourse (Putri et al, 2017;D. N. Sari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Outputs that discussed knowledge variables were tested using questionnaires related to all aspects that adolescents know about reproductive health and knowledge of premarital sex behavior. Of the 14 articles that had been reviewed, there were 10 articles that discussed the influence of knowledge, namely articles (Alfiyah et al, 2018;Ayu et al, 2019;Mahmudah et al, 2016;Mariani & Arsy, 2017;Putri et al, 2017;Rizki & Amalia, 2019;D. N. Sari et al, 2018;Siregar & Handayani, 2018;Ulfah, 2018;Yolanda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The same data also showed that 14.4% of men and 5.6% of women had consumed alcohol, then it was also found that 2.6% of men had used drugs [7,8]. Another description of health risk factors is sexual behavior where 8.26% of male students and 4.17% of female students aged 12-18 years have had sexual intercourse [9]. Premarital sexual behavior certainly has a broad impact on adolescents, especially related to the transmission of infectious diseases and unwanted pregnancies and abortions [5,10].…”
Section: A Introductionmentioning
confidence: 94%